NTRK fusions in osteosarcoma are rare and non‐functional events - Baptiste Ameline; Karim H Saba; Michal Kovac; Linda Magnusson; Olaf Witt; Stefan Bielack; Michaela Nathrath; Karolin H Nord; Daniel Baumhoer (Wiley, 2020)
Abstract Neurotrophic tyrosine receptor kinase (NTRK) fusions are promising molecular targets that have been described in a broad range of malignant tumours. Fusions commonly lead to the expression of chimeric proteins with constitutive tyrosine kinase activation that drives tumorigenesis. Despite a low prevalence among most solid tumours (<1%), the first encouraging results with pan‐NTRK tyrosine kinase inhibitors (TKIs) such as larotrectinib or entrectinib stimulated the search for eligible patients. Here, we report the first three cases of osteosarcoma harbouring NTRK fusions, among 113 patients sequenced. It is also the first report on NTRK fusions within a tumour type characterised by highly rearranged genomes and abundant passenger mutations. Whereas the presence of NTRK gene fusions in many tumours is considered to be one of the main driver events for tumour progression, the three chimeric transcripts described here appear non‐functional and likely represent randomly occurring passenger alterations. Particularly in tumours with complex karyotypes, it may therefore be advisable to specifically investigate the fusion transcripts for functional impact before considering targeted treatment approaches using pan‐NTRK TKIs.